Integrated microfluidics-based construction of anti-BTN2A2 gel droplet cell preparations for non-invasive tumor-infiltrating lymphocyte therapy - Yishen Tian; Jingxuan Li; Na Yang; Yang Zhao; Jiancao Zuo; Hang Xiong; Yiwen Pan; Li Xiao; Min Su; Feng Han; Zhixu He; Rong Hu (Materials Today Bio)
Tumor infiltrating lymphocyte therapy (TIL therapy) is one of the effective treatments for solid tumors. However, certain periods or sites of solid tumors are not amenable to surgical resection. Meanwhile, the abundant and dense extracellular matrix (ECM) and regulatory cells (e.g., regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSC)) in solid tumors when infused back into the treatment will prevent T cell infiltration and proliferation, thus inhibiting the efficacy of this approach. In this study, a novel cell preparation was successfully developed by integrating microfluidic chip design with carbodiimide chemical modification. This preparation was surface modified with BTN2A2 antibodies and internally contained T cells isolated from the blood of tumor hosts, along with simulated collagen peptide CMP. Specifically, the cell preparation exerted its anti-tumor effects through multiple mechanisms: Firstly, the surface BTN2A2 antibodies effectively inhibited the proliferation of Tregs and MDSCs within the tumor microenvironment; Secondly, leveraging the T cell antigen receptors (TCRs) present in the blood T cells, which were similar to those of tumor-infiltrating lymphocytes, significantly enhanced their targeting and cytotoxic capabilities; Furthermore, the CMP component within the droplets effectively promoted the infiltration of T cells into tumor tissues. In the complex immunosuppressive microenvironment, the synergistic action of these components markedly enhanced the clearance efficacy of the immune system. Experimental results demonstrated that this cellular preparation exhibited promising therapeutic effects in both melanoma and pancreatic cancer models. This research provided a novel platform for the synergistic cooperation of various methods in tumor immunotherapy, holding broad application prospects.